The effect of substrate and arc voltage on the structure and functional behaviour of NiTi shape memory alloy produced by wire arc additive manufacturing. (October 2021) - Ponikarova, I.; Palani, I.A.; Liulchak, P.; Resnina, N.; Singh, S.; Belyaev, S.; Mani Prabu, S.S.; Jayachandran, S.; Kalganov, V.; Sahu, Anshu; Bikbaev, R.; Karaseva, U.
Abstract: This paper aimed to study the influence of the substrate and the arc voltage on the structure and functional properties of the NiTi shape memory alloy produced by wire arc additive manufacturing (WAAM). The gas metal arc based WAAM process was used for the deposition of 3-layered NiTi walls on a titanium or steel substrate at different arc voltages using a Ni50.9 Ti49.1 wire. It was found that in the sample deposited on the Ti substrate, the Ti2 Ni phase appeared and the Ti concentration in the NiTi phase increased to 50.5 at.%. An increase in the arc voltage influenced the volume fraction of Ti2 Ni precipitates in the 1st layer but hardly affected the chemical composition of the NiTi phase in all layers as a result, the martensitic transformation temperatures do not depend on the arc voltage. Therefore, the deposition of the Ni-rich NiTi wire on a Ti substrate allowed for the production of the Ti-rich NiTi walls undergoing the martensitic transformation and demonstrated the shape memory behaviour at high temperatures. An increase in the arc voltage hardly affected the shape memory behaviour but decreased the strain up to failure due to an increase in the volume fraction of the brittle Ti2 Ni phase, which in turn facilitated the formation of cracks during deformation. In the sample deposited on the steel substrate, the NiTiFe solid solution and Ti-C, Ni3 Ti4, and Ni3 Ti2 precipitates formed in the 1st layer. An increase in the arc voltage led to an increase in the Fe concentration in the NiTiFe solid solution from 17 at.% to 42 at.% in the 1st layer. From layer to layer, the Fe concentration decreased; however, it remained larger than 1.5 at.% and completely suppressed the martensitic transformation and the shape memory effects in the NiTi sample deposited on the steel substrate.